Immature stages of Hamadryas fornax fornax (Hübner) (Lepidoptera: Nymphalidae: Biblidinae) - Salik,Lucy Mila Garcia (2015)
ABSTRACT The external morphology and biology of the immature stages of Hamadryas fornax fornax (Hübner, [1823]) (Lepidoptera, Nymphalidae, Biblidinae) recorded on Dalechampia triphylla (Euphorbiaceae) in Curitiba, Paraná, Brazil are described. Morphological characters are illustrated and described, as a result of observations in scanning electron, stereoscope and optical microscopes, the last two attached to a camera lucida. Results are compared and discussed with immature stages of other species of Biblidinae.